Penerapan Model Cased Based Reasoning Dalam Mendeteksi Gejala Kerusakan Mesin Mobil - Mutammimul Ula; Ilham Saputra (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2022)
The application of the cased based reasoning model in detecting symptoms of car engine damage can occur at any time. This is due to the condition of the car being poorly maintained, never having regular and periodic service. Therefore, a system is needed to see the damage to the car and the symptoms that cause the car to be damaged. the system can display the results of the diagnosis contained in the symptoms that arise. The purpose of this study is to detect car damage and provide alternative solutions for car owners in checking engine damage and how to handle it. The symptoms used in the detection of car damage are the ignition system, fuel system, cooling system, lubrication system, exhaust system and the result is that the highest level of damage is detected as a solution in handling it. damage occurs to the ignition system consisting of wasteful fuel, the engine falters, idling is damaged, acceleration is fast and the engine is difficult to start, based on the fault diagnosis there is an error in the car's spark plug and the solution is to replace the spark plug according to the repair manual and use free fuel lead (first). the ignition system value is 0.565217391, the fuel system value is 1, the cooling system value is 0.5, the lubrication system value is 0.56, the exhaust system value is 0.7. The highest case value is 1 with a spark plug replacement solution. The results of this study can analyze the diagnosis of damage to the car engine and car owners can find solutions to the damage, such as damage to the engine starting from the type of damage, early symptoms, characteristics of damage, diagnosis and solutions or ways of repair